Work-Life Balance Memoderasi Equity Sensitivity dan Internal Locus of Control Pada Perilaku Etis Auditor - Darmawan, I Putu Ari; Widanaputra, Anak Agung Gde Putu (E-Jurnal Akuntansi; Vol 32 No 4 (2022), 2022)
The purpose of the study was to examine and analyze the work-life balance variable moderating equity sensitivity and internal locus of control on the ethical behavior of auditors. The research uses ethical theory as a grand theory. The sample used was 77 auditors. Sampling using purposive sampling as a sampling technique. The analysis technique uses Partial Least Square (PLS). The results showed that work-life balance was able to moderate the effect of equity sensitivity and internal locus of control on the ethical behavior of auditors. Research contributes to the importance of the role of work-life balance in the ethical behavior of auditors. Keywords: Ethical Behavior; Equity sensitivity, Internal locus of control; Work-life balance; Ethical Theory.